Teacher Training & Assistance in Creating Creative Learning Media Using the Canva Application : Pelatihan & Pendampingan Guru dalam Pembuatan Media Pembelajaran Kreatif Menggunakan Aplikasi Canva - Iwan Abdy; Dwi Widyastuti Nurharyanto; Hutri Handayani Isra; Irham Wibowo; Roni Kurniawan (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Era 5.0 has greatly influenced all aspects of life, including education. Era 5.0 is an era where all activities have experienced digitalization. In the education sector, digitalization is carried out on learning devices. One way to do this is by using the Canva application. The Canva application has several advantages: it is easy to access via various gadgets, and teachers have been given special access to get a premium account. Based on this, the Khairun University FKIP service team held a service at SDN 48 Ternate City. The service activity is "Training and Mentoring Teachers in Making Creative Learning Media using the Canva Application". This activity will occur from 15 May to 17 June 2024, starting at 09.00 WIT - 16.10 WIT, and will occur in class IV at SDN 48 Ternate City. This school was chosen because it is a school that is partnered with the Khairun University Primary School Teacher Education (PGSD) study program. The result of this socialization activity is an article published as a form of publication of the activity. The wider community can access this article as an example of activities that train teachers to have digital awareness. Furthermore, this activity hopes that learning integrated with technology with the aim of the independent curriculum to form a generation with a global perspective can be realized.